Nonsyndromic with Recurrent Idiopathic Gingival Fibromatosis: A Rare Case Report - Kumari, Amrita (Int J Clin Pediatr Dent, 2021)
Idiopathic gingival fibromatosis is a genetic rare disorder, which is characterized by a progressive enlargement of the gingiva. Gingival enlargement is an overgrowth of the gingiva, which can be caused by various etiological factors such as poor oral hygiene, plaque accumulation, inadequate nutrition, hormonal stimulation, several blood dyscrasias, or long-term intake of certain drugs like phenytoin, nifedipine, or cyclosporine. A 14-year-old female patient reported to the Department of Periodontology, Mahatma Gandhi Dental College and Hospital, Jaipur, Rajasthan with her chief complaint of swollen gums in both upper and lower arches since 3 years, which was gradual in onset and increased in size since 4 months which covered almost half of the surface of each tooth. Also reported that 3 years ago, there was similar swelling for which surgical intervention in form of gingivectomy was carried out. The treatment plan for this case was followed by phase 1 therapy (scaling and root planing) and after completion of phase 1 therapy, the labial tissue from the mandibular anterior region was excised and sent for histopathological examination. Histopathological appearance revealed idiopathic gingival fibromatosis. Thereafter, the conventional gingivectomy under local anesthesia was performed to remove excess gingival overgrowth. How to cite this article: Kumari A, Bansal MB, Asrani KH, et al. Non-syndromic with Recurrent Idiopathic Gingival Fibromatosis: A Rare Case Report. Int J Clin Pediatr Dent 2021;14(1):158–160.